The Adequacy of Pelvic Lymphadenectomy During Radical Cystectomy for Carcinoma Urinary Bladder: A Narrative Review of Literature - Jena, Rahul; Shrivastava, Nikita; Sharma, Aditya Prakash; Choudhary, Gautam Ram; Srivastava, Aneesh (Frontiers in Surgery, 2021)
An adequate pelvic lymph node dissection (PLND) is an essential part of radical cystectomy for muscle invasive bladder cancer. However, the definition of what constitutes an adequate PLND is often shrouded in controversy. Various authors have defined different anatomic templates of PLND based on levels of pelvic lymph nodes. Some have suggested other surrogate markers of the adequacy of PLND, namely lymph node count and lymph node density. While individual studies have shown the efficacy and reliability of some of the above markers, none of them have been recommended forthright due to the absence of robust prospective data. The use of non-standardized nomenclature while referring to the above variables has also not helped in making the answer clear. Most of older data seems to favor use of extended template of PLND over the standard template. On the other hand, one recent randomized controlled trial (RCT) did not show any benefit of one template over the other in terms of survival benefit, but the study design allowed for a large margin of bias. Therefore, we conducted a systematic search of literature using EMBASE, Medline and Pubmed using PRISMA-P checklist for articles in English Language published over last 20 years. Out of 132 relevant articles, 47 were included in the final review. We have reviewed existing literature and guidelines and have attempted to provide a few suggestions towards a uniform nomenclature for the various anatomical descriptions and the extent of PLND that should be done while doing a radical cystectomy. The results of another large RCT (SWOG S1011) are awaited and until we have more definite evidence, we should adhere to these suggestions as much as possible and deal with each patient on a case to case basis.